Discursividade de professores de língua inglesa sobre o ensino-aprendizagem na Educação de Jovens e Adultos - Nascimento, Mariana Ruiz (2020)
Considering that the English language is part of the curriculum of Youth and Adult Education (YAE) in Brazil, the present research started from the hypothesis that, when enunciating about the teaching-learning of English in this modality, the discourse of teachers reveals tense representations and conflicts about the processes of teaching and learning in this context. Therefore, this research aimed to investigate the discourse of English language teachers of Uberlândia when they enunciate about the teaching-learning process in YAE. For that, we outlined some discursive representations of these teachers when they enunciate about YAE and English language teaching-learning process; we analyzed the discursive inscriptions that constitute and support these representations; problematized the voices that support the representations of these teachers and their decision-making when enunciating about YAE and teaching-learning processes. This research was based on the studies of Applied Linguistics, French Discourse Analysis, and Dialogic Discourse Analysis. To collect the data, we used the Analysis of Discursive Resonances in Open Statements (AREDA), created by Serrani-Infante (1998a), and the corpus was composed of six testimonies of English language teachers from Uberlândia who work or have worked in YAE for at least one semester. Considering the history of YAE, it is understood that the educational movements related to YAE in Brazil produce discourses that build the discourse about YAE and affect the processes of identification, and they rarely differ from the memory around teaching in YAE. After analyzing and discussing the representations, we conclude that it is possible that the discourse of English language teachers of YAE constitutes a tense-conflicting event because they expect the student, placed as different than the regular one, to follow the same teaching standard imposed in regular education and achieve the same results; they are teachers who do not see English teaching being possible in YAE, which can lead them to question why they are there; if only the native speaker knows the language, and the teacher needs it to teach, the teaching-learning processes become unattainable and incomplete in their view; the YAE student lacks something, a lack that the teachers cannot fill. Furthermore, unfortunately, YAE is still seen more like a “repair” modality aimed at the “less capable” instead of a field of promotion and realization of the right to education.